الفروق الجوهرية بين غرامة التأخير والاشتراط بإيجاب الصدقة (دراسة فقهية مقارنة ): The jurisprudentia difference between imposing fine for late payments and asking for Sadaqa (Khairulummah, 2022)
This study aims to explain the rooting of the "delay fine" Linguistically and idiomatically by considering the two terms and considering an additional compound, and the image of the requirement to obligate charity in the contract so that their concept is distinguished with high accuracy, and to review the ideas of Muslims scholars and their opinions regarding these two issues in terms of permissibility and prohibition, by looking at their evidence for what they deduce, and the discussions that were received on it, and the most correct opinion in it, and refer to the decisions and fatwas that were issued in it by the scientific bodies and the jurisprudence councils at the present time as possible. .
Keywords: financial fine, obligation to obligate charity, Islamic jurisprudence, Islamic banks.